Bee Sting Envenomation: Rare Fatality - Sethi, Sudhansu Sekhar; Jena , Manoj Kumar (Journal of Indian Academy of Forensic Medicine, 2015)
Among the invertebrates, insects, particularly hymenoptera, most commonly cause anaphylaxis. In stinging bees, wasps and ants, the ovipositor of female has been modified into a stinger. Honey bees leave behind their barbed stinger in the victim’s body and eventually die by evisceration. Bee sting in most of the situations is potentially serious, the severity and duration of reaction varies from one person to another depending on location and no of bee stings received. The spectrum of bee sting disease ranges from local reaction to death. Stings from bees usually cause a transient local reaction which may last for several days and generally resolves without treatment. Occasionally death may occur mostly due to anaphylactic shock. Non anaphylactic causes of death are mainly due to multi organ failure. Honey bee sting is responsible for large number of casualty in tropical and subtropical countries.